Assessment of Potential Area in Jakarta Capital City Based on Land Performance Weighting - Rosantiningsih, Ika; Hasan, Chotib (Journal of Strategic and Global Studies, 2024)
Law of the Republic of Indonesia No. 3 of 2022 concerning the National Capital has a major impact on Jakarta, challenges for Jakarta to response the relocation of the capital. Jakarta strives to become a Global City by increasing investment, various efforts are made for increasing and economic stabilitation, in line with the sustainable development goals, "Decent Work and Economic Growth". Investment is closely related to spatial planning. Jakarta publish Governor Regulation No. 31 of 2022 concerning the Spatial Planning Detailed, that have using performance assessment with infrastructure services (transportation, road, and public infrastructure factors) weighting, but limited to use in trade and service zones, has not been applied to all subzones. To capture wider investment potency, performance assessment using land-based weighting is needed such as: Land use and planning; Property Right and Value, and Land Safety. The research aims to obtain weights that can be used in performance assessment to be applied to an area in determining the potential value of the area from the land aspect. The method used uses a mixed method in the form of interviews, then the use of Analytical Hierarchi Process (AHP) in the form of questionnaires with informants and respondents from various stakeholders such as central and local governments, representatives of urban planner associations, developers from various sectors, and academics, followed by data processing in Expert Choice. The results of weighting land-based performance assessments as a quick assessment in determining the potential of the area for investment development and priorities in infrastructure development.